Virtual Reality and Correctional Rehabilitation: A Game Changer. (September 2019) - Ticknor, Bobbie
Virtual reality (VR) has been used for learning and treatment for decades. Few efforts have been made to incorporate this technology into correctional rehabilitation. Advances in VR systems, reductions in price, and the broader availability of the technology now make this effort more attainable. This article introduces readers to VR and explains how it can be used to enhance current efforts in offender treatment.